2008
DOI: 10.1145/1341971.1341975
|View full text |Cite
|
Sign up to set email alerts
|

Environmental influences on gender in the IT workforce

Abstract: In an effort to better understand the underrepresentation of women within the IT profession, one promising line of investigation is the influence of factors in the socio-cultural environment. In order to examine this topic, we draw on data from a multi-year field study of women IT professionals in three regions of the U.S.: Massachusetts, North Carolina and Pennsylvania. We employ Trauth's (2000) conceptual framework of environmental influences on the development of a region's information economy to consider e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(21 citation statements)
references
References 33 publications
0
21
0
Order By: Relevance
“…In their work related to organizational interventions, Trauth and her colleagues Trauth et al, 2009;Trauth, Quesenberry, & Yeo, 2008) used an individual differences model to account for the diversity of women's experiences in IT. The authors posited that socio-cultural influences operate on an individual level to shape how women experience and respond to barriers.…”
Section: Workplace Interventionsmentioning
confidence: 99%
See 2 more Smart Citations
“…In their work related to organizational interventions, Trauth and her colleagues Trauth et al, 2009;Trauth, Quesenberry, & Yeo, 2008) used an individual differences model to account for the diversity of women's experiences in IT. The authors posited that socio-cultural influences operate on an individual level to shape how women experience and respond to barriers.…”
Section: Workplace Interventionsmentioning
confidence: 99%
“…Trauth et al (2009) identified specific intervention strategies to address the barriers of work-life balance, lack of mentoring, and organizational climate. Trauth et al (2008) revealed women's own methods to address barriers and preserve their personal agency. More recently, revealed the importance of leadership and management support, as well as equitable policies regarding pay and evaluation, in creating flexible interventions to meet the diversity of needs among IT women.…”
Section: Workplace Interventionsmentioning
confidence: 99%
See 1 more Smart Citation
“…The theory chosen to inform this research is the Individual Differences Theory of Gender and IT because it provides the conceptual tools to examine variation in perceptions about the IT field [36] [37] [45]. The original application of this theory was to explain withinfemale variation in the influence of individual, institutional and societal factors on female participation in the IT field [42] [44] [46]. Because of its focus on within-gender variation due to individual and group effects, this theory has also been used to explore within-gender variation resulting from the intersectionality of gender and other identity characteristics such as race.…”
Section: Methodsmentioning
confidence: 99%
“…Trauth et al . (2008b) analysed data on female IT professionals in three US regions to find that two environmental factors, economy and culture, influenced female participation in the IT workforce.…”
Section: Theories Of Gender and Itmentioning
confidence: 99%